Strategi Pengembangan Emping Jagung Untuk Optimalisasi Potensi Lokal di Desa Lawanganagung - Solekhah, Afifatul Aprilia Yani; Lutfiyah, Fanny; Shoffrianto, Achmad Fadlan Prima; Syafarinda, Aldiva; Prasetya, Sandy Tri; Badi'ah, Roudlotul; Abdillah, David Fahmi; Abadi, Muhammad Dzikri (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2025)
MSMEs play an important role in the Indonesian economy, but many villages, including Lawanganagung Village, face challenges in optimizing their local potential. Therefore, the purpose of this community service project is to develop a strategy for corn chip product growth through rebranding, flavor diversification, and repackaging to enhance its appeal and marketability. This community service initiative employs training and the Participatory Learning and Action (PLA) method, which includes surveys, focus group discussions, implementation, and evaluation. The outcomes of the community service activities in Lawanganagung Village include the creation of innovative corn chip flavor variants, such as chocolate, sweet and spicy balado, and caramel boran, as well as modernized packaging and branding under the name